2017
DOI: 10.21608/zvjz.2017.7866
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Studies on Bone Marrow Derived Stromal Stem Cells on Liver Injuries in Rats

Abstract: Liver is a remarkable vital organ, it is responsible for metabolizing the different food elements, filtering and detoxifying poisons in the blood to remove numerous toxic compounds. Liver affections are essentially caused by harmful chemicals (certain anti-infection, paracetamol, carbon tetrachloride, aflatoxins, per oxidized oil and so on.), overabundance utilization of liquor, immune system issue and disease. Up till now, orthotropic liver transplantation is the most powerful treatment of liver infections. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Dowidar and colleagues [43] demonstrated that the transplantation of bone marrow-derived MSCs (BM-MSCs) could treat acetaminophen liver injury by the enhancement of hepatocyte regeneration and inhibition of liver stress and inflammatory signaling in the rat model. Besides BM-MSCs, researchers have found that adipose tissue-derived MSCs (AT-MSCs) also have hepatic differentiation potential in vitro and in vivo [44,45].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Dowidar and colleagues [43] demonstrated that the transplantation of bone marrow-derived MSCs (BM-MSCs) could treat acetaminophen liver injury by the enhancement of hepatocyte regeneration and inhibition of liver stress and inflammatory signaling in the rat model. Besides BM-MSCs, researchers have found that adipose tissue-derived MSCs (AT-MSCs) also have hepatic differentiation potential in vitro and in vivo [44,45].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…ASCs are multipotent stem cells and have a more limited cell differentiation potential than ESCs. ASCs considered for liver regeneration are liver stem cells (LSCs) [13,14] and mesenchymal stem cells (MSCs) [15,16] from different tissue sources, such as bone marrow (BM-MSCs) [17], adipose tissue (ADSCs) [18][19][20], umbilical cords (UC-SCs), peripheral blood, cartilage, etc. MSCs show low immunogenicity, have a self-renewal ability, are easily obtainable, and can be used without ethical issues, which make them the perfect candidate for liver regeneration [21].…”
Section: Introductionmentioning
confidence: 99%